Appendix 2.8: The Detainee Mariflor Parpan - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
The following cables show (1) the response of the Marcos regime to dissent, even by those who are not connected to either the CPP-NPA or the MNLF; (2) that in some instances, rumors of torture did turn out to be untrue; and (3) that Imelda Marcos appeared to know very well what happened in the detention centers during martial law. The letter from Mariflor Parpan’s brother affirms the perception that Imelda Marcos could intervene to release certain detainees.